A fructose receptor gene influences development and feed intake in Helicoverpa armigera. (22nd December 2021) - Ai, Dong; Dong, Chenxi; Yang, Bin; Yu, Caihong; Wang, Guirong
Abstract: Gustatory receptors (GRs) are critical for multiple life activities of insects. Owing to the rapid development of genome and transcriptome sequencing, numerous insect GRs have been identified. However, the expression patterns and functions of these receptors are poorly understood. In this study, we analyzed the expression pattern of GRs in Helicoverpa armigera and found that the fructose receptor HarmGR9 was highly expressed in the foregut and abdomen. The function of HarmGR9 was identified using the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) system. Knockout of the HarmGR9 gene shortened the developmental period of the larval stages and increased food consumption in both larvae and adults. This study revealed the tissue distribution of sugar‐sense‐related receptors in H. armigera and thereby expanded the understanding of insect feeding regulation. Abstract : Gustatory receptors (GRs) are critical to multiple life activities in insects. In this study, we analyzed the expression pattern of GRs in Helicoverpa armigera and found that the fructose receptor HarmGR9 was highly expressed in the foregut and abdomen. Knocked‐out HarmGR9 gene shortened the developmental period of larvae stages and increased the food consumption in both larvae and adults.